The Roots of “Brown Sahib Medical Men’s” Burden - Ruhil, Rohini (Indian Journal of Community Health, 2015)
Background: Bhore Committee was setup at a time of great capitalism crisis – the Second World War. In India, there was an acute emergence of the nationalist movements at that time. Indian people were being oppressed under the British colonial rule for more than 200 years and their socio-economic conditions were very poor. The health conditions of Indian people at that time were reflection of their socio-economic conditions and were very poor. India had a severe shortage of human resource for healthcare. Subsequently Bhore Committee and Sokhey Committee gave their recommendations which were further reviewed in 1959 by Mudaliar committee. Aims and Objectives - This review article aims to critically compare the strategies for developing human resource for health; proposed by the Bhore Committee, Sokhey Committee, and the Mudaliar Committee reports; and to discuss their implications. Material and Methods: Rigorous literature review was done to extract the information. Thematic analysis was done to generate main themes and sub-themes. The paper was then structured, analysed and concluded at the end. Results and Conclusion: The medical education today has become the privilege of English speaking, urban based, rich, upper class and caste students. On the other hand majority of downtrodden section of society got buried under the burden of “Brown Sahib medical men” such trends divide the society in to an upper class of English proficient intellectuals riding on the backs of lower class who can only sell its labour.